Case Report: A rare homozygous patient affected by TTR systemic amyloidosis with a prominent heart involvement - Micaglio, Emanuele; Santangelo, Gloria; Moscardelli, Silvia; Rusconi, Daniela; Musca, Francesco; Verde, Alessandro; Campiglio, Laura; Bursi, Francesca; Guazzi, Marco (Frontiers in Cardiovascular Medicine, 2023)
Hereditary transthyretin amyloidosis is a severe, adult-onset autosomal dominant inherited systemic disease predominantly affecting the peripheral and autonomic nervous system, heart, kidney, and the eyes. We present a case of a Caucasian 65-year-old man with cardiac amyloidosis and the homozygous mutation Val142Ile (classically, Val122Ile) in the transthyretin gene. We provide a genotype-phenotype correlation regarding the genetic status of both heterozygous and homozygous individuals and their clinical conditions at the time of genetic testing.